Pengaruh Kualitas Produk terhadap Pemilihan Vendor di PT. Hitachi Power Systems Indonesia - Khanifan Budhy Luhur; Sutandi Sutandi (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This research was conducted at PT. Hitachi Power Systems Indonesia. The purpose of this research is to determine the results of data analysis of the effect of Product Quality on Vendor Selection at PT. Hitachi Power Systems Indonesia by distributing questionnaires of 40 respondents. The research methodology used is quantitative descriptive research method. The analysis results show the value of t-count> t-table (5.478> 1.685). This means that Ho is rejected and H1 is accepted, or there is an influence between Product Quality and Vendor Selection. And from the results of calculations using SPSS version 20, the coefficient of determination (R2) shows the value of R Square = 0.441.This means that the Product Quality variable (X) can explain or explain the Vendor Selection (Y) of 44.1%, the remaining 55.9% ( from the calculation of 100% -44.1%) influenced by other variables not included in the model or equation in this study.The analysis results show the value of t-count> t-table (5.478> 1.685). This means that Ho is rejected and H1 is accepted, or there is an influence between Product Quality and Vendor Selection